ANALYSIS OF THE EFFECT OF FRICTION OF THE WORKING BODIES OF KNITTINGMACHINES ON THE WEDGES LIFE CYCLE - PLESHKO, SERHII; KOVALIOV, YURII; KHYNEVYCH, RUSLAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In this paper, we present the results of research on the evaluation of the knitting machine working bodies (needles, wedges, stitches) friction effect on the wear of working surfaces of wedges and on their life cycle. The object of research was to analyse the effect of friction of needle-wedge and needle-stitch pairs (guide needles) on the intensity of wear of working surfaces of wedges, which determines their life cycle. Modern methods of theoretical research based on the theory of friction and wear and the theory of designing knitting machines were used to resolve the problems. Increased efficiency of knitting machines can be achieved by reducing the friction losses of the working bodies of the knitting mechanism (mainly needle-wedge and needle-stitch friction pairs).  Therefore, the task of this research is to analyse the effect of friction of the working bodies of the knitting machine on the wear of the working surfaces of wedges and on their life cycle. The analysis of obtained results shows that the friction of working bodies significantly affects the wear of wedges of knitting machines and, accordingly, their life cycle.The rational mode of operation of the KO-type circular knitting machine is its mode when the ratio of friction of the needle-wedge and needle-stitch pairs is within 0.08...0.1 (which is achieved by choosing appropriate type of lubricant and lubrication modes of the knitting mechanism). At the same time, the life cycle of the stitch cam ranges from 208.79 ∙ 103 to 76.97 ∙ 103 hours (from 16,312 to 6,013 days at 2-shift operation of the machine).With the existing mode of operation of the KO-2 circular knitting machine, as shown by research, the life cycle of the stitch cams does not exceed 9 ∙ 103 hours (703 days)
Keywords: knitting machine; needle; wedge; stitch; friction; wedge wear; wedge life cycle